2023
DOI: 10.3390/nu15030553
|View full text |Cite
|
Sign up to set email alerts
|

Serum Nutritional Biomarkers and All-Cause and Cause-Specific Mortality in U.S. Adults with Metabolic Syndrome: The Results from National Health and Nutrition Examination Survey 2001–2006

Abstract: Background: There is limited research on the associations between serum nutritional biomarkers and mortality risk in patients with metabolic syndrome (MetS). Existing studies merely investigated the single-biomarker effect. Thus, this study aimed to investigate the combined effect of nutritional biomarker mixtures and mortality risk using the Bayesian kernel machine regression (BKMR) model in patients with MetS. Methods: We included the MetS patients, defined according to the 2018 Guideline on the Management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Nitrogen serves as an indicator of protein consumption. The intake of proteins holds paramount importance for the human body, as they serve numerous essential functions that greatly contribute to maintaining overall health and well-being (Peng et al 2023 ). These roles encompass a wide array of physiological processes that are vital for optimal functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen serves as an indicator of protein consumption. The intake of proteins holds paramount importance for the human body, as they serve numerous essential functions that greatly contribute to maintaining overall health and well-being (Peng et al 2023 ). These roles encompass a wide array of physiological processes that are vital for optimal functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The reported positive effects of beta-carotene have the ability to prevent and control the oxidative stress that found in diseases such as T2DM (5). In addition, abnormalities of micronutrients with antioxidant properties such as beta-carotene may be associated with MetS and the progression of MetS (33). A systematic review and meta-analysis (2) reported a strong inverse association of serum total carotenoids and beta-carotene with MetS occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al (12) examined the association between serum carotenoid levels and the risk of cardiovascular disease mortality in patients with type 2 diabetes and found that higher serum b-carotene concentrations were significantly correlated with increased risk of cardiovascular mortality in diabetic patients. However, Peng et al (13) investigated the relationship between serum nutritional biomarkers and the risk of all-cause mortality and cause-specific mortality in individuals with metabolic syndrome and the results indicated that a-carotene may be the primary protective biomarker against mortality risk in individuals with metabolic syndrome, while folate and vitamin B12 were not associated with mortality risk in metabolic syndrome population.…”
Section: Introductionmentioning
confidence: 99%
“…However, Peng et al. ( 13 ) investigated the relationship between serum nutritional biomarkers and the risk of all-cause mortality and cause-specific mortality in individuals with metabolic syndrome and the results indicated that α-carotene may be the primary protective biomarker against mortality risk in individuals with metabolic syndrome, while folate and vitamin B12 were not associated with mortality risk in metabolic syndrome population.…”
Section: Introductionmentioning
confidence: 99%